Dinamika Keahlian dan Gender dalam Komite Audit: Dampaknya pada Manajemen Laba - Huda, Misbahul; Sutrisno, Catur Ragil; Prasetiani, Titi Rahayu (Universitas Negeri Padang, 2024)
Purpose – The research aimed to identify and assess the impact of two types of expertise—accounting and finance—along with gender in the audit committee on earnings management practices. The control variables included leverage, audit committee size, and company size.Design/methodology/approach – The research focused on 47 banking companies listed on the Indonesia Stock Exchange (IDX). The sample was chosen using purposive sampling based on specific criteria, resulting in the selection of 27 companies. Over the 2017-2021 observation period, 135 data were collected, with 2 outliers being removed, leaving 133 observations for analysis. Partial Least Square (PLS) is used as an analysis tool.Findings – Research conducted proves that expertise has a different influence on earnings management. Accounting skills have a significant positive effect while financial skills have a significant negative effect. Gender within the same committee does not significantly impact earnings management. Testing of the control variables reveals that the size of the audit committee and company size have no effect on earnings management, while leverage shows a significant negative impact.Originality/value –This research offers a new contribution in understanding the role of expertise by distinguishing the influence of accounting expertise and financial expertise. This approach offers a more in-depth understanding of the distinct roles of different expertise and audit committee gender on earnings management, particularly within the banking sector listed on the Indonesia Stock Exchange. Additionally, the study investigates leverage, audit committee size, and firm size as control variables.Research limitations/implications – The research only focuses on banking entities listed on the IDX and the observation period is 5 years. This study shows results that contradict the initial hypothesis regarding accounting expertise and gender, so that further research can examine more deeply about other factors that can influence earnings management. This can serve as a reference for various stakeholders in making more informed decisions regarding corporate governance, particularly concerning the composition and expertise of audit committee members.